Test validity of periodic liver function tests in a population of Japanese male bank employees - Yano, Eiji; Tagawa, Kazumi; Yamaoka, Kazue; Mori, Masaki (Journal of clinical epidemiology, 2001)
The validity (sensitivity and specificity) of annual liver function tests, determined by assaying blood levels of aspartate aminotransferase, alanine aminotransferase and gammaglutamyl transpeptidase, was evaluated using the results of health checkups of male bank workers. The specificity of each liver function test to detect persons with fatty liver, excess alcohol users, and hepatic virus carriers, diagnosed respectively by ultrasound, detailed inquiry, and virus marker tests, was always higher than 80%, except for alanine aminotransferase in excess alcohol users (63.5%). However, the highest sensitivity to detect virus carriers was alanine aminotransferase to detect HCV antibody-positive workers, but it was only 45.5%. The highest sensitivity of the liver function tests to detect excess alcohol users in obese subjects was only 33.3%. The highest sensitivity by liver function tests to detect fatty liver was 35.7% which was inferior to that of the body mass index. These results indicate that the liver function tests mandated in the workplace periodic health checkups in Japan exhibit very low sensitivity for the detection of any of the proposed target clinical conditions.